EFFECT OF OXYTOCIN MASSAGE THROUGH THE BACK ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Safa'ah, Nurus; Putri Ryandini, Tiara; Pitaloka, Dyah; Mubin, Muhammad (Lux Mensana: Journal of Scientific Health, 2022)
Introduction.Every minute one Indonesian baby dies because they do not get breast milk in the first hour of birth, problems with breastfeeding can be due to milk production not coming out. One way to overcome the non-smooth milk production is by doing oxytocin massage through the back. This massage can relax the mother so that it stimulates the oxytocin reflex and smooth milk production. The purpose of this study was to determine the effect of oxytocin massage through the back on breast milk production in postpartum mothers. Method.This study uses a Quasy Experimental design involving 50 respondents who were taken by Systematic Random Sampling. Respondents were divided into 2 groups, namely the control group with 25 respondents and the experimental group with 25 respondents. Collecting data using a checklist observation. Data were analyzed using Paired simple T-test with a significant level of 0.05. Result&Analysis.This study showed that there is an effect of oxytocin massage through the back on breast milk production in postpartum mothers with p value = 0.000 (< 0.05). Discussion. Oxytocin massage through the back can stimulate the reflex hormone oxytocin. It is hoped that health workers can provide health education about oxytocin massage through the back to the community so that later it is hoped that all people will be able to apply oxytocin massage through the back to overcome the inability to produce breast milk.